Nosocomial COVID-19 Infection in Acute Neurological Diseases at the Indonesian National Referral Hospital - Mesiano, Taufik; Tunjungsari, Dyah; Budikayanti, Astri; Ramli, Yetty (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2023)
Introduction: Neurological diseases elevate the susceptibility to respiratory tract ailments. This study aims to evaluate the incidence of nosocomial coronavirus disease 2019 (COVID-19) among non-COVID neurology inpatients and identify associated risk factors. Objective: To assess nosocomial COVID-19 infection in non-COVID neurology inpatients and identify associated risk factors. Material and Methods: A prospective cohort study was conducted during the initial wave of the COVID-19 pandemic, encompassing all non-COVID neurology inpatients at Dr. Cipto Mangunkusumo Hospital from May to September 2020. Clinical data were collected, and bivariate and multivariate analyses were employed to examine risk factors. Result and Discussion: Among 308 subjects, 31 (10.6%) experienced nosocomial COVID-19 infection. Suspect cases constituted 77.4%, probable cases 16.1%, and confirmed cases 6%. Predominant neurological diseases included cerebrovascular disease (36.7%), CNS neoplasm (18.8%), and traumatic brain injury (15.6%). Comorbid diseases increased the infection risk by 6.53 times (95% CI 1.52-28.0), particularly non-CNS malignancy (12.37, 3.7-41.00), chronic pulmonary TB (12.29, 2.7-55.89), and hypertension (3.8, 1.3-11.4). Loss of consciousness and nasogastric tube (NGT) usage elevated the risk by 2.92 (1.37-6.21) and 4.68 (1.95-11.24) times. This study reinforces existing evidence that hospitalized patients with neurological diseases are more susceptible to COVID-19, particularly due to loss of consciousness and NGT usage. The risk is amplified with comorbidities such as non-CNS malignancy, chronic pulmonary TB, and hypertension. Conclusion: Individual neurological diseases alone did not heighten the risk of COVID-19 infection. Notably, factors like loss of consciousness, NGT usage, and comorbid diseases significantly correlate with nosocomial COVID-19 infection in non-COVID neurology inpatients.